Analisis Prefensi Konsumen dan Kualitas dalam Melakukan Pembelian Terhadap Produk Skincare di Kota Palopo - Nurul Mutia; Suhardi M.Anwar; Rahmawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the factors that influence consumer preferences for skincare products in Palopo City. This study uses a quantitative method with a non-probability approach and purposive sampling technique to obtain a representative sample, considering the population is not known with certainty. The sample used in this study amounted to 150 respondents, selected based on the criteria of skincare users in Palopo City. Data were collected through an online questionnaire distributed using the snowball sampling technique through social media. The questionnaire consisted of 20 measurement items related to the constructs of creative self-efficacy, knowledge sharing, innovative work behavior, and employee performance, using a Likert scale of 1 to 4. Data analysis was carried out using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique, which allows testing of causal relationships between latent concepts in a theoretical model. The results of this study provide insight into consumer preferences for skincare products and the factors that influence them, and show the important role of social media influence in purchasing decisions.